2009
DOI: 10.1002/ajim.20792
|View full text |Cite
|
Sign up to set email alerts
|

Airways obstruction among older construction and trade workers at Department of Energy nuclear sites

Abstract: Our study of construction workers employed at DOE sites demonstrated increased COPD risk due to occupational exposures and was able to identify specific exposures increasing risk. This study provides additional support for prevention of both smoking and occupational exposures to reduce the burden of COPD among construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 54 publications
4
58
0
2
Order By: Relevance
“…The spirometric criteria included were non-uniform. GOLD criteria II+ was the most prevalent (92)(93)(94)(95). The FEV 1 and FEV 1 /FVC were the outcome in two studies (91,97), like FEV 1 /FVC<0.7 and <LLN (96,98).…”
Section: Publications Since the Initial Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…The spirometric criteria included were non-uniform. GOLD criteria II+ was the most prevalent (92)(93)(94)(95). The FEV 1 and FEV 1 /FVC were the outcome in two studies (91,97), like FEV 1 /FVC<0.7 and <LLN (96,98).…”
Section: Publications Since the Initial Reviewmentioning
confidence: 96%
“…Five of these (91)(92)(93)(94)(95) were cross-sectional and three (96)(97)(98) were longitudinal with a follow-up time between 5-13 years. Six studies came from Europe (91,92,94,(96)(97)(98) and one study each from the US (93) and South Africa (95).…”
Section: Publications Since the Initial Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have indicated increased risk for COPD in a number of occupations, including rubber, plastics, leather, textile, and paper manufacture, wood industry, transportation, mining, and construction [6,7]. In regard to the occupational exposures, statistically significant association with COPD was demonstrated with exposure to asbestos, silica, welding fumes, cement dusts, and some tasks associated with exposures to paints, solvents, and removal of paints [8]. Furthermore, Bergdahi et al [9] demonstrated an increased mortality from COPD in construction workers exposed to inorganic dust that was more expressed in never smokers.…”
Section: Introductionmentioning
confidence: 99%